A COMPARISON OF MAJOR ELEMENTS BETWEEN MARINE SEDIMENTS AND IGNEOUS ROCKS: AS A BASIC DETERMINATION OF THE SEDIMENT SOURCE AT UJUNG PENYUSUK WATERS, NORTH BANGKA,BANGKA BELITUNG PROVINCE - Ediar Usman (Marine Geological Institute of Indonesia, 2010)
Three igneous rock samples from the coast and five sediments from the marine of Ujung Penyusuk Waters have been used for chemistry analysis as the basic determination of sediment source. The result of chemistry analysis shows that the major element with relatively same pattern. In the igneous rock samples, the result of chemistry analysis shows the SiO2 ranges between 72.3 - 76.8%, Al2O3 (9.64 - 11.64%), and Fe2O3 ( 2.08 - 2.18%). In the marine sediment, the content of SiO2 is between 62.2 and 66.5%, Al2O3 (2.93 - 3.63%) and Fe2O3 (21.19 - 24.40%). Other elements such as CaO, MgO, K2O, Na2O and TiO2 are relatively similar values in all samples. The difference of element content in marine sediment and coastal igneous rock occurs in Al2O3 and Fe2O3. The Al2O3 is small in marine sediment while the Fe2O3 is higher compared to igneous rocks. Decreasing of the Al2O3 (kaolinite) in the marine sediment is caused by the character of the Al2O3 that was derived from quartz rich of igneous rocks forming kaolinite. It was than deposited in the sea floor. Increasing of the Fe2O3 in marine sediment is caused by addition reaction of the Fe from the sea. Generally, the content of the SiO2 (quartz) in igneous rock and marine sediment belongs to the same group source that is acid igneous rock. The SiO2 in the sediment belongs to a group of granitoid. Keywords: major elements, marine sediment, igneous rock, Ujung Penyusuk waters Tiga contoh batuan dari pantai dan lima contoh sedimen dari dasar laut di perairan Ujung Penyusuk, Bangka Utara telah digunakan untuk analisis kimia sebagai dasar dalam penentuan sumber sedimen. Hasil analisis kimia menunjukkan kandungan unsur utama dengan pola yang relatif sama. Pada contoh batuan beku, hasil analisis kimia memperlihatkan kandungan SiO2 antara 72,3 - 76,8%, Al2O3 (9,64 – 11,64%) dan Fe2O3 (2,08 - 2,18%). Pada sedimen dasar laut memperlihatkan kandungan SiO2 antara 62,2 – 66,5%, Al2O3 (2,93 – 3,63%) dan Fe2O3 (21,19 - 24,40%). Unsur lainnya seperti CaO, MgO, K2O, Na2O dan TiO2 yang relatif sama pada seluruh contoh. Perbedaan kandungan pada sedimen dasar laut dan batuan beku di pantai terjadi pada unsur Al2O3 dan Fe2O3. Kandungan Al2O3 pada sedimen dasar laut lebih kecil dan Fe2O3 lebih besar dibandingkan pada batuan beku. Berkurangnya Al2O3 (kaolin) pada sedimen dasar laut disebabkan oleh sifat Al2O3 yang berasal dari rombakan batuan beku yang kaya kuarsa (SiO2) membentuk kaolin. Unsur tersebut kemudian diendapkan di dasar laut. Peningkatan Fe2O3 pada sedimen dasar laut disebabkan oleh penambahan unsur Fe2O3 yang mengikat unsur Fe dari berbagai mineral di laut. Secara umum, kandungan SiO2 (kuarsa) dalam batuan beku dan sedimen dasar laut termasuk dalam kelompok yang relatif sama yaitu batuan beku asam. SiO2 dalam sedimen termasuk kelompok granitoid. Kata kunci: senyawa utama, sedimen dasar laut, batuan beku, Perairan Ujung Penyusuk.